2019
DOI: 10.1021/acs.iecr.9b00312
|View full text |Cite
|
Sign up to set email alerts
|

Development of Copolyamide-66/6 Cross-Linked Foams by a One-Step Reactive Extrusion Process

Abstract: The simultaneous chemical cross-linking and foaming of aliphatic copolyamide by one-step reactive extrusion using a bifunctional trialkoxysilaneimidazoline additive is studied. The aim was to reach efficient melt strength enhancing the cell growth without coalescence. From liquid NMR analyses, the cross-linked foam synthesis was evidenced resulting from both imidazoline ring opening (further reacting with the polyamide carboxylic acid endgroups) and alkoxysilane hydrolysis−condensation reactions (leading to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The 1 H NMR spectra traces, see Figures 1 & 2, were performed to ascertain the chemical structure of DFA-BDA X HMDA Y and DFA-BDA X HMDA Y (co)polyamides. 42 In the 1 3B and D). Generally, the amide groups of the PAs favor the formation of a H−bond while the introduction of shorter chain length diamines (EDA or BDA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 H NMR spectra traces, see Figures 1 & 2, were performed to ascertain the chemical structure of DFA-BDA X HMDA Y and DFA-BDA X HMDA Y (co)polyamides. 42 In the 1 3B and D). Generally, the amide groups of the PAs favor the formation of a H−bond while the introduction of shorter chain length diamines (EDA or BDA).…”
Section: Resultsmentioning
confidence: 99%
“…The M n , M w, and PDI of the PAs were determined by employing GPC. The M n , monomer feed ratio, and acid/amine values are also determined by 1 H NMR spectra and the data are summarized in Tables S2 and S3. It can be seen from Table S3 that the M w of the DFA-EDA X HMDA Y and DFA-BDA X HMDA Y range from 14,007 to 34, 243 g/mol and from 39, 533 to 44,191 g/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous copolymers have been studied in recent years, and their syntheses are well known, for example, lactam‐lactam, [ 87 ] lactam‐lactone, [ 88 ] and lactone‐lactone. [ 89 ] The production of copolyamides via manufacturing processes such as reactive extrusion [ 90 ] and casting [ 91 ] has also been reported in literature. To date, only one academic study has been reported on using copolymers as a matrix for the production of composites via TP‐RTM.…”
Section: Future Trends Of Thermoplastics Systemsmentioning
confidence: 99%
“…9−11 However, traditional polyamide materials have a strong tendency to crystallize, which result in insufficient melt strength during high melting, thus seriously hindering the effective use of sc-CO 2 foaming in such systems. 12,13 Multiple methods, such as filler insertion, 14,15 chain extension, 16,17 and reactive crosslinking, 18 have been proposed to enhance the sc-CO 2 foaming performance of polyamides. However, despite effectively improving the properties of foaming materials, strategies involving the introduction of fillers or additives are often associated with process cost and dispersion problems.…”
Section: Introductionmentioning
confidence: 99%